Nurse Recruitment in Conflict-Prone Areas: Systematic Review - Basri Basri; Dianis Wulan Sari; Ferry Efendy; Ucik Nurmalaningsih (Indonesian Journal of Global Health Research, 2024)
Recruitment of nurses in conflict zones often raises issues, and recruitment techniques are always difficult to adapt to the challenges that may arise in conflict environments (Sadhaan et al., 2022). The recruitment process of nurses in conflict areas often focuses on staffing needs, without considering other important criteria such as lack of information, transparency about the work environment, minimal security support, and lack of recruitment standards that are more appropriate to conflict conditions. (The lack of nurses' desire to work in conflict areas is a multifaceted problem that is influenced by various factors, including conflict management, working conditions, career expectations and systemic barriers (T. Pono et al., 2023). The purpose of this systematic review is to determine the impact of nurse recruitment for conflict areas. This study was conducted using 15 literature selections using the PRISMA approach to analyze 15 articles taken from 4 databases: Clarivate, SAGE, Pubmed, Scopus in 2019-2024. The keyword combinations used were: (“Conflict Impact” OR “Conflict Area” AND “Nurse Recruitment”). In assessing the bias and methodological quality of the articles obtained, this study used the Joanna Briggs Institute (JBI) critical assessment with a bias score range of 75-100%. Out of 856 articles, 15 research articles met the inclusion criteria of nurses' experience working in conflict areas. The conclusion of this study is that the recruitment of nurses in conflict-prone areas shows that the main challenges include security, the urgent need for medical personnel, and specialized skills in handling crisis situations. in this case, recruited nurses must have high adaptability and training in stress management and medical techniques in emergency conditions.